A validated age-related normative model for male total testosterone shows increasing variance but no decline after age 40 years. - Thomas W Kelsey; Lucy Q Li; Rod T Mitchell; Ashley Whelan; Richard A Anderson; W Hamish B Wallace (PLoS ONE)
The diagnosis of hypogonadism in human males includes identification of low serum testosterone levels, and hence there is an underlying assumption that normal ranges of testosterone for the healthy population are known for all ages. However, to our knowledge, no such reference model exists in the literature, and hence the availability of an applicable biochemical reference range would be helpful for the clinical assessment of hypogonadal men. In this study, using model selection and validation analysis of data identified and extracted from thirteen studies, we derive and validate a normative model of total testosterone across the lifespan in healthy men. We show that total testosterone peaks [mean (2.5-97.5 percentile)] at 15.4 (7.2-31.1) nmol/L at an average age of 19 years, and falls in the average case [mean (2.5-97.5 percentile)] to 13.0 (6.6-25.3) nmol/L by age 40 years, but we find no evidence for a further fall in mean total testosterone with increasing age through to old age. However we do show that there is an increased variation in total testosterone levels with advancing age after age 40 years. This model provides the age related reference ranges needed to support research and clinical decision making in males who have symptoms that may be due to hypogonadism.